Growth optimization, optical, and dielectric properties of heteroepitaxially grown ultrawide-bandgap ZnGa2O4 (111) thin film - Karmakar, Subrata; Emu, Injamamul Hoque; Halim, Md Abdul; Sarkar, Pallab Kumar; Sultana, Maria; Tasnim, Ayesha; Hamid, Md Abdul; Shiam, Istiaq Firoz; Droopad, Ravi; Haque, Ariful (Journal of applied physics, 2024)
Ultrawide bandgap ZnGa2O4 (ZGO) thin films were grown on sapphire (0001) substrates at various growth temperatures with a perspective to investigate the electrical and optical characteristics required for high-power electronic applications. Due to the variation in the vapor pressure of Zn and Ga, severe loss of Zn was observed during pulsed laser deposition, which was solved by using a zinc-rich Zn0.98Ga0.02O target. A pure phase single-crystalline ZGO thin film was obtained at a deposition temperature of 750 °C and an oxygen pressure of 1 × 10−2 Torr. The out-of-plane epitaxial relationship between the sapphire and ZGO thin film was obtained from φ-scan. The x-ray rocking curve of the ZGO thin film grown at 750 °C exhibits a full width at half maximum of ∼0.098°, which indicates a good crystalline phase and quality of the thin film. Core-level x-ray photoelectron spectroscopy of ZGO grown at 750 °C indicated that Zn and Ga were in the 2+ and 3+ oxidation states, respectively, and the atomic ratio of Zn/Ga was estimated to be ∼0.48 from the fitted values of Zn-2p3/2 and Ga-2p3/2. The high-resolution transmission electron microscopy images revealed a sharp interface with the thickness of the ZGO film of ∼265 nm, and the signature of minor secondary phases was observed. The bandgap of the ZGO film at different growth temperatures was calculated from the ultraviolet-diffuse reflectance spectroscopy spectra, and its value was obtained to be ∼5.08 eV for the 750 °C grown sample. The refractive index (n) and the extinction coefficient (k) were determined to be ∼1.94 and 0.023 from the ellipsometric data, respectively, and the real dielectric function (ɛr) was estimated to be ∼6.8 at energy 5 eV. The ultrawide bandgap and dielectric function of ZGO recommend its possible potential applications in deep-ultraviolet optoelectronic devices and high-power electronics.